Historical charcoal additions alter water extractable, particulate and bulk soil C composition and stabilization - Abdelrahman, H.; Hofmann, D.; Berns, A.E.; Meyer, N.; Bol, R.; Borchard, N. (Wiley, 2018)
The objective of this work was to investigate the chemical composition and the quantitative changes in soil organic matter (SOM) fractions in response to multiple historical inputs of charcoal that ceased > 60 years ago. The topsoil (0–5 cm) and subsoil (5–20 cm) samples of charcoal enriched soils and the unamended reference soils were assessed for C and N contents in bulk soil, particulate organic matter (POM) fractions and water extractable organic matter (WEOM). The SOM molecular characteristics were investigated in the solid phase by nuclear magnetic resonance (NMR) and in the WEOM by Fourier transform ion cyclotron resonance mass spectrometry (FT‐ICR‐MS). Formerly added charcoal additions reduced the extracted amount of WEOM and altered POM pattern: an increased proportion of C and N stored in coarse, intermediate, and fine POM relative to corresponding total C and N was found in subsoils. In contrast, C and N stored in the residual fraction (< 20 µm) decreased. NMR results revealed a higher aromaticity of SOM in charcoal enriched soils, while the FT‐ICR‐MS results indicated an increased presence of lignin‐ and tannin‐like compounds in the WEOM of these soils. Former charcoal additions enhanced soils capacity to retain and stabilize C and N. Particularly, the presence of charcoal particles elevated C and N stored in large POM fractions > 20 µm, which presumably increases soil porosity and thus the soils' capacity to retain water.